Investigation of vitamin c preservation in melons during long-term storage - Степаненко, Дмитро Сергійович (Eastern-European Journal of Enterprise Technologies, 2014)
The melons of Zolotistaya and Bereginya varieties of average ripening period were under experimental studies. One of the electron-ion technology methods was applied for storage. This method implies processing fresh fruits before storage in the air, ionized by electric current of corona discharge. In addition, fruits were packed in shrink wrap (SW). Two types of packaging were used: full and partial (leaving empty space around the fruit base and stem). For determining the influence of ionized air (IA) on preservation of vitamin C in melons, the fruits, fully and partially packed in SW without the IA treatment were laid down for storage. The fruits without packaging and treatment were used as control samples. The control samples were stored both in natural conditions (at the temperature of 20 – 25 0С) and in the refrigerator (at the temperature of +3 0С and the relative humidity of 85 %). Taking into account the importance of preserving ascorbic acid for as long time as possible, its dynamics was studied. The analysis of the obtained results showed that using the melon storage method stabilizes metabolism in fruits and partially disinfect their surface. It was found that the use of ionized air prolongs shelf life and favors relatively high preservation of vitamin C. Shrink wrapping positively effects the preservation of biochemical fruit constituents. It protects them from mechanical damages and impedes penetration of pathogenic organisms from one package into another. The scientific literature gives no information about melon storage in ionized air. The lack of dynamics patterns for basic biochemical indicators of fruits during storage creates certain difficulties in predicting the product life terms and yield at the final stage with the best given organoleptic indicators and biological value. Therefore, there are no doubts concerning the appropriateness of conducting studies in this field.